Contribution of the Facilities Completeness and Learning Interests on Student Practical Capabilities in Broad-Based Network Technology Subject - Novajri, Kardimen; Maksum, Hasan; Indrawan, Eko; Irfan, Dedy (LPPM Undiksha, 2021)
Based on the preliminary observations that have been done, it was found that the students' practice skills were still low in the area-based network technology subject. Based on the agreed value standard, the minimum score in productive subjects is 80, so the results of the students' practical capability show that it has not been fully achieved. This research is qualitative research with a correlational approach, which aims to reveal how much the practical facilities completeness and students' interest in learning to practical skills in the area-based network technology subject. The population of this study was students of class XI, which consisted of 34 students. At the same time, the sample was taken from a population of 25 students. The data was collected using a questionnaire, and the value of practice and the data were analyzed using correlation and regression techniques. Based on the data analysis, it was found that: completeness of practical facilities contributed 28% to practical skills, learning interest contributed 34.2% to practical capabilities, completeness of practical facilities and interest in learning together contributed 82.3% to the ability practice.